Purification and properties of individual collagenases from Streptomyces sp. strain 3B - Petrova, D; Derekova, A; Vlahov, S (Folia microbiologica, 2006)
Streptomyces strain 3B constitutively secreted collagenolytic enzymes during the post-exponential growth phase. Purification is described here leading to two collagenases (I and II) with specific activity of 3350 and 3600 U/mg, respectively, the highest activity obtained as yet for any streptomycete collagenase. Analysis of the purified enzymes by the method of zymography revealed that both I and II were homogeneous, with molar mass 116 and 97 kDa, respectively. Both collagenases were identical in their pH (7.5) and temperature optimum (37 degrees C). The inhibition profile of the enzymes by EDTA and 1,10-phenanthroline confirmed these enzymes to be metalloproteinases. By testing the activity with insoluble collagen, acid soluble collagen, gelatin, casein, elastin and Pz-PLGPR it was established that I and II are very specific for insoluble collagen and gelatin, showing a high activity toward acid soluble collagen and Pz-PLGPR. However, collagenases I and II failed to hydrolyze casein and elastin; they belong to true collagenases and resemble the clostridial enzymes.
Keywords: Collagenases; koncentrace vodíkových iontů; Temperature; kolagenasy; substrátová specifita; teplota; Hydrogen-Ion Concentration; Substrate Specificity; Streptomyces